Transient Analysis of Switching the Distributed Generation Units in Distribution Networks - Mehrnoosh Vatani (Institute of Advanced Engineering and Science, 2016)
Adding distributed Generators (DGs) to the passive electrical networks causes major changes in the specifications of the network including voltage profile, short circuit level and transient stability. In this paper, the effect of DGs switching transient in network is considered. The DGs location are changed in different buses. Two types of DGs are used (i.e. wind and synchronous DGs). Switching transient signals are time variant. It has a continuous spectrum of frequency. Fast Fourier and Wavelet transform methods are used for transient analysis. The proposed method is applied to IEEE-13 Bus distribution system.